Strong and Weak Convergence for Asymptotically Almost Negatively Associated Random Variables - Aiting Shen; Ranchao Wu (Discrete Dynamics in Nature and Society)
The strong law of large numbers for sequences of asymptotically almost negatively associated (AANA, in short) random variables is obtained, which generalizes and improves the corresponding one of Bai and Cheng (2000) for independent and identically distributed random variables to the case of AANA random variables. In addition, the Feller-type weak law of large number for sequences of AANA random variables is obtained, which generalizes the corresponding one of Feller (1946) for independent and identically distributed random variables.